Characterization of eosinophilic esophagitis variants by clinical, histological, and molecular analyses: A cross‐sectional multi‐center study. Issue 8 (17th February 2022) - Greuter, Thomas; Straumann, Alex; Fernandez‐Marrero, Yuniel; Germic, Nina; Hosseini, Aref; Yousefi, Shida; Simon, Dagmar; Collins, Margaret H.; Bussmann, Christian; Chehade, Mirna; Dellon, Evan S.; Furuta, Glenn T.; et al.
Abstract: Objective: Physicians are increasingly confronted with patients presenting with symptoms of esophageal dysfunction resembling eosinophilic esophagitis (EoE), but absence of significant esophageal eosinophilia. The purpose of this study was to characterize and classify this group of EoE variants. Design: Patients from six EoE‐centers with symptoms of esophageal dysfunction, but peak eosinophil counts of <60/mm 2 (<15/hpf) in esophageal biopsies and absence of gastro‐esophageal reflux disease (GERD) were included. Clinical, endoscopic, (immuno)‐histological, and molecular features were determined and compared with EoE, GERD, and healthy controls. Results: We included 69 patients with EoE variants. Endoscopic abnormalities were found in 53.6%. We identified three histological subtypes: EoE ‐ like esophagitis (36/69, 52.2%), lymphocytic esophagitis (14/69, 20.3%), and non ‐ specific esophagitis (19/69, 27.5%). Immunohistochemistry revealed—in contrast to EoE—no significant increase in inflammatory cell infiltrates compared with GERD and healthy controls, except for lymphocytes in lymphocytic esophagitis. EoE‐typical Th2‐response was absent in all EoE variants. However, considerable structural changes were detected based on histology and protein expression. Using next generation mRNA sequencing, we found the three EoE variants to have distinct molecular fingerprints partially sharing pronounced traits of EoE. Hierarchical sample clustering of RNA sequencing data confirmed the presence of an EoE‐like (characterized by eotaxin‐3 expression), non‐specific, and lymphocytic variant cluster (characterized by CD3 cells and TSLP expression). Conclusion: All EoE variants are clinically and histologically active conditions despite the absence of esophageal eosinophilia. EoE variants appear to be part of a disease spectrum, where classical EoE represents the most common and apparent phenotype. Abstract : This study assesses clinical, (immuno)‐histological, and molecular characteristics of 69 patients with EoE‐related symptoms, but absence of significant esophageal eosinophilia. We identify three histological variants, EoE‐like esophagitis, lymphocytic esophagitis, and non‐specific esophagitis. All three variants show decreased LEKTI expression, while lymphocytic esophagitis also shows CD3‐positive cell invasion. RNA sequencing reveals distinct molecular fingerprints in each variant and confirms the presence of an EoE‐like, lymphocytic, and non‐specific variant/cluster. Abbreviations: CD3, cluster of differentiation 3; EoE, eosinophilic esophagitis; Eos, eosinophil; HPF, high‐power field; LEKTI, lympho‐epithelial Kazal‐type‐related inhibitor; RNA seq, RNA sequencing